Hadith #146 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Abdullah bin 'Amr bin al-'Aas; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Kathir bin Marrah al-Hadrami كثير بن مرة الحضرمي; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي (Sunan Ibn Majah)
“I saw the Messenger of Allah during the campaign of Tabuk performing ablution, washing each part once.”
Grade:

Hadith #772 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Abu Hameed al-Sa'idi al-Ansari; Amarah bin Ghazya bin al-Harith عمارة بن غزية بن الحارث; Amr bin 'Uthman عمرو بن عثمان بن عفان; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Rabi'ya bin Abi 'Abdur Rahman (Sunan Ibn Majah)
“I saw the Messenger of Allah (ﷺ) performing prayer both barefoot, and while wearing sandals.”
Grade:

Hadith #1220 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Asim bin 'Umar bin Qatada al-Ansari عاصم بن عمر بن قتادة; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Mahmud bin Labid bin 'Uqba; Rafi' bin Khadij bin Rafi' (Sunan Ibn Majah)
“Do not delay the funeral once it is ready.”
Grade:

Hadith #1378 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Abdullah bin Basr al-Maazni; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Yazid bin Khumayr al-Rahbi يزيد بن خمير (Sunan Ibn Majah)
“Ramadan began, and the Messenger of Allah (ﷺ) said: ‘This month has come to you, and in it there is a night that is better than a thousand months. Whoever is deprived of it is deprived of all goodness, and no one is deprived of its goodness except one who is truly deprived.’”
Grade:

Hadith #2092 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Kathir bin Marrah al-Hadrami كثير بن مرة الحضرمي; Khalid bin Ma'dan خالد بن معدان; Mu'adh ibn Jabal (Sunan Ibn Majah)
“Whoever finds his exact property with a man who has become bankrupt, and then he has more right to it than anyone else.”
Grade:

Hadith #2332 - Sunan Ibn Majah - Abd al-Whab bin al-Dhak عبد الوهاب بن الضحاك بن أبان; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Makhul al-Shami/al-Damashiqi مكحول الشامي; Sulaiman bin Musa al-Ashdaq سليمان بن موسى الأموي الأشدق; Wathla bin al-'Asqa' (Sunan Ibn Majah)
He said: “What is taken from the tree and carried away, its value and the like of it along with it (meaning double its price must be paid). What (is taken) from the place where dates are dried, (the penalty) is cutting off the hand if the amount taken is equal to the price of a shield. But if (the person) eats it and does not take it away, there is no penalty.” He said: “What about the sheep taken from the pasture, O Messenger of Allah (ﷺ)?” He said: “(The thief) must pay double its
Grade: